2023
DOI: 10.1038/s41598-023-28801-y
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment and metal contamination in fish, water and soil sediments in the East Kolkata Wetlands, India, Ramsar site

Abstract: East Kolkata Wetlands (EKW) is an important site for fish culture in sewage-fed areas, which are major receivers of pollutants and wastages from Kolkata. EKW is internationally important as the Ramsar site was declared on Aug 2002 with an area of 125 km2. EKW is a natural water body where wastewater-fed natural aquaculture has been practiced for more than 70 years. It is ecologically vulnerable due to the discharge of toxic waste through sewage canals from cities. Assessing the EKW to understand the inflow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…The highest amount of Zn was found in the muscles of Poropuntius laoensis (2,101.00 mg/ kg). The levels of Zn recorded in the gills of the examined fish in this study were higher than those reported in some selected literature (Table 3) except for the report of [34] in Labeo rohita collected at Kolkata wetland, India. Based on the values obtained, Zn concentrations found in gills of all fishes are below the proposed limit by the FAO/WHO [31] for human consumption of toxic compounds.…”
Section: Levels Of Trace Metals In Fish Speciescontrasting
confidence: 87%
See 2 more Smart Citations
“…The highest amount of Zn was found in the muscles of Poropuntius laoensis (2,101.00 mg/ kg). The levels of Zn recorded in the gills of the examined fish in this study were higher than those reported in some selected literature (Table 3) except for the report of [34] in Labeo rohita collected at Kolkata wetland, India. Based on the values obtained, Zn concentrations found in gills of all fishes are below the proposed limit by the FAO/WHO [31] for human consumption of toxic compounds.…”
Section: Levels Of Trace Metals In Fish Speciescontrasting
confidence: 87%
“…The higher Manganese concentrations may be as a result of addition from agricultural runoff, sewage which causes anemia and kidney damage. The values obtained for Mn in this study were higher than those reported by [34] with 1.92 mg/L and [36] in both dry (3.73 mg/L) and wet (4.27 mg/L) season collected from Ogbere River, Ibadan.…”
Section: Levels Of Trace Metals In Water Samples In Mg/lcontrasting
confidence: 79%
See 1 more Smart Citation
“…Contamination of aquatic systems has led to major environmental and health issues for both humans and aquatic animals. 1,2 Anthropogenic activities have increased the concentration of metals in natural water, impacting aquatic animals and subsequently human health. 3,4 Inorganic pollutants, such as metals, possess specific properties like dispersal, bioaccumulation, and biomagnification within aquatic food chains.…”
Section: Introductionmentioning
confidence: 99%
“…Metals are significant pollutants in aquatic ecosystems that affect aquatic organisms, including fish. Contamination of aquatic systems has led to major environmental and health issues for both humans and aquatic animals 1,2 . Anthropogenic activities have increased the concentration of metals in natural water, impacting aquatic animals and subsequently human health 3,4 .…”
Section: Introductionmentioning
confidence: 99%